Quality statistics in banking reforms for national transformation - Sarah O. Alade (CBN Journal of Applied Statistics, 2012)
This paper outlines the important role of statistics in aiding proper planning and achievement of sustainable economic development. The paper elaborates the importance of investing in quality and reliable statistics for policy design and implementation and stresses the vital role statistical information play in effective operation in both private and public sector in every economy. The role of quality, reliable and timely information to a well-functioning financial system and as a guide to monetary policy making is illustrated in the paper. The paper credits accurate statistical information to the success of the Nigerian banking sector reform. However, it suggests that in Nigeria, while considerable progress has been made in improving the gathering and processing of statistical data, more needs to be done to sensitize the general public on vital role of statistics in economic planning and monitoring of policy implementations.
Keywords: 330